Umbilical Keloid Formation in the Port Site Post Laparoscopy - Kaushik Bhattacharya; Simran Kaur; Vishal Kumar; Sushant Kumar Yadav (National Board of Examinations Journal of Medical Sciences)
A rare entity of keloid formation in the umbilical port site after undergoing laparoscopic cholecystectomy is being highlighted.